Profil Interaksi Verbal Pasien Penyakit Jantung Koroner dalam Berkomunikasi - Amanah Rakhim Syahida (Universitas Muhammadiyah Ponorogo, 2019)
Coronary heart patients are very strong subjects in the research of verbal interaction profiles. Because a lot of verbal interactions must be understood by patients as communicators. Simple communication theory to find this interaction has several elements, namely Communicator, Message (Message), Channel, Communicative, and Feed back. This type of research uses qualitative descriptive methods including observations in the location of the safira panjen Malang Main clinic, in-depth interviews with coronary heart patients who were included in the informant's criteria as a sample, namely Mr. Suryadi who had long been treated as a coronary heart disease patient, as the primary informant , and supporting informants namely the closest person and specialist doctor and then data analysis. The results of this study can be concluded 1.) the profile of verbal interaction of coronary heart patients in communicating has Determinism the use of verbalization generally has conditions directed to meet the desired goals of coronary heart patients (communicators) in expressing messages in the form of language, symbols, chennel in the form of senses and HP in communicating, Feed Back with communicants, this leads to healing, and verbal interactions of a coronary heart patient (communicator) experience repeated conditions with the assumption that using Indonesian or Javanese language kromo inggil, Channel, Feed back given by communicant in this is like; family environment, workplace and physician at the same time) in Communicating Coronary Jatung Patients who finally get the full understanding and comfort and discomfort to influence their health condition, 2.) Obstacles are also experienced in interacting which lead to Polarization, Evaluation of Stasis in Coronary Heart Patients, Stereotypes Between Patients with Coronary Hearts (Communicators) with their communicants.